The Niemann–Pick C1 Protein of Patients with Hepatocellular Carcinoma Is Associated with Survival Time in Males and Tumor Size in Females - Florian Weber; Katja Evert; Alexander Scheiter; Sophie von Sachsen-Coburg; Kirsten Utpatel; Christa Buechler (Biomedicines)
Background/Objectives: The Niemann–Pick C1 (NPC1) protein regulates cellular cholesterol homeostasis, which is disrupted in hepatocellular carcinoma (HCC). Sex differences in cholesterol metabolism may also be related to NPC1 expression in HCC. A sex-specific analysis was, therefore, performed to investigate this further. Methods: The expression of NPC1 protein in hepatocytes was assessed using immunohistochemistry in HCC tissues from 264 male and 59 female patients, as well as in non-tumor tissues from 41 males and 7 females. Results: The disease etiology was documented for 40% of these patients, and NPC1 protein levels in the tumors of patients with alcoholic, metabolic, and viral liver disease were comparable. The severity of underlying liver fibrosis was similar in both females and males. No difference in hepatocyte NPC1 protein expression was observed between males and females in non-tumor and tumor tissues. However, NPC1 expression was strongly increased in tumor tissues in both sexes. NPC1 protein levels were positively associated with T stage and Union for International Cancer Control (UICC) stage in both sexes. NPC1 protein levels were negatively correlated with overall survival, recurrence-free survival, and metastasis-free survival time in males only. Univariate Cox regression analysis showed a significant association of NPC1 protein levels with metastasis-free survival in males. Positive correlations of NPC1 protein with tumor size and negative associations with tumor inflammation were observed only in women. Conclusions: This study showed that hepatocyte NPC1 protein levels are highly elevated in HCC tissue in both sexes but are more closely associated with survival in male patients than in female patients.